Pengaruh Kompetensi Profesional Guru Terhadap Hasil Belajar Siswa (Studi Kasus Di SD Islam Darunnajah) - Mastur; Manaf, Sofwan; Samiyono; Ahmad Farid, Zaki; Salmy, Muskhairillah (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
The purpose of this study was to build a model of the phenomenon and research gap in increasing learning outcomes that can be increased with teacher professional competence in Islamic Religious Education lessons at SD Islam Darunnajah Jakarta. The study used a descriptive quantitative method with a cause and effect method. The population of the study was 206 students in grades 5 and 6 of SD Islam Darunnajah. Sampling using the SEM model was at least 5-10 times the number of indicators, so that the sample was 96 respondents. Data analysis used SmartPLS. The results of the study showed that teacher professional competence had a positive and significant effect on learning outcomes. While the R-Square value was 0.402, which means that learning outcomes were influenced by professional competence by 40.2% while the remaining 59.8% were influenced by other variables. The need for ongoing training to develop teacher creativity in designing learning strategies is very important. School management support, such as adequate resources and a forum for sharing experiences between teachers, will strengthen this effort. With these steps, it is expected that teacher professionalism will increase, giving a positive impact to students and educational institutions.